A systematic review on the WHO's Global Priority Pathogens (GPP) List reported in animals, products, and by-products in Colombia - Cardozo Herrera, Laura K; Vásquez Jaramillo, Laura; Correa Valencia, Nathalia M (Revista Colombiana de Ciencias Pecuarias, 2024)
Background: The World Health Organization (WHO) published in 2017 a global priority pathogens (GPP) list for research and development of effective antibiotics. It is a catalog of bacteria that should be prioritized in the fight against antibiotic resistance. Objective: To collect and assess the scientific evidence on bacteria listed as GPP in animal food products and by-products in Colombia, identifying knowledge gaps and providing evidence-based recommendations. Materials and Methods: This review was conducted following PRISMA guidelines. Only original articles published in peer-reviewed journals were considered. Results: Twenty-one articles published between 2001 and 2021 met the inclusion criteria. The geographical areas of study were in the provinces of Antioquia, Cundinamarca (including Bogotá district), Santander, and Tolima. The main bacteria reported from the WHO´s list were fluoroquinolone-resistant Salmonella, methicillin-resistant and vancomycin-intermediate and resistant Staphylococcus aureus, and carbapenem-resistant ESBL-producing Enterobacteriaceae. The sources were feces, facilities, equipment, feed, animal drinking water, bedding material, animal tissues, and carcasses from broiler, laying hen, cattle, and pig production systems. Conclusion: Our findings enhance the understanding of the current dynamics of bacterial resistance in Colombia. Nevertheless, several aspects need to be further researched, such as defining standardized methods for microbiological identification in veterinary medicine, as well as evaluating antibiotic susceptibility patterns of bacteria in accordance to what is done in humans, among other aspects.